Journalism and the culture of othering - Allan, Stuart (Brazilian journalism research, 2015)
In seeking to render problematic traditional conceptions of journalistic identity, this article critiques the seemingly natural, even ‘common sensical’ structures of social exclusion recurrently underpinning its formulation. More specifically, it explores, firstly, a series of insights provided by feminist and gender-sensitive critiques of journalism. In assessing the typically subtle imperatives of sexism in news reporting, it considers the extent to which journalistic identity continues to be defined within the day-to-day ‘macho culture’ of the newsroom, where female journalists’ perceptions of sexual discrimination typically vary sharply from those held by their male colleagues. Secondly, attention turns to the issue of ethnic diversity, where the need to deconstruct the racialised projection of ‘us and them’ dichotomies precisely as they are taken-up and re-inflected in news reporting is shown to be of pressing concern. In bringing together these respective set of debates, primarily from British and US contexts, this article aims to contribute to conceptual efforts to further unravel the ways in which journalists’ routine, everyday choices about what to report – how best to do it, and why –involves them in a politics of mediation, one where all too often a culture of othering proves significant.